Safety evaluation of an extension of use of the food enzyme 4‐α‐glucanotransferase from the non‐genetically modified Aeribacillus pallidus strain AE‐SAS - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2024)
Abstract The food enzyme 4‐α‐glucanotransferase (1,4‐α‐d‐glucan:1,4‐α‐d‐glucan 4‐α‐d‐glycosyltransferase, EC 2.4.1.25) is produced with the non‐genetically modified Aeribacillus pallidus strain AE‐SAS by Amano Enzyme Inc. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in two food manufacturing processes. Subsequently, the applicant requested to extend its use to two additional processes. In this assessment, EFSA updated the safety evaluation of this food enzyme for use in a total of four food manufacturing processes. As the food enzyme–total organic solids (TOS) is removed from the final foods in one food manufacturing process, the dietary exposure to the food enzyme–TOS was estimated only for the remaining three processes. Dietary exposure was up to 0.040 mg TOS/kg body weight (bw) per day in European populations. When combined with the no observed adverse effect level reported in the previous opinion (900 mg TOS/kg bw per day, the highest dose tested), the Panel derived a margin of exposure of at least 22,500. Based on the data provided for the previous evaluation and the revised margin of exposure, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.